Diagnostic algorithm in patients with complicated forms of the abdominal aortic aneurysm - O. V. Buchnieva (Ukrainian Journal of Cardiovascular Surgery, 2019)
In patients with complicated forms of aneurysm of the abdominal aorta, the study of the features of the clinical course, errors in the diagnosis of the underlying disease at the stages of medical care, as well as the diagnostic value of instrumental methods of research. Direct and indirect signs of complicated forms of aneurysm of the abdominal aorta are determined. Based on the results of the study, an algorithm for diagnosing patients with aortic aneurysm in the abdominal aorta was developed, depending on the state of hemodynamics at the stages of provision of medical care.